Analisis Sifat Mekanik Komposit Serat Sabut Kelapa Sebagai Material Alternatif Pengganti Kayu Untuk Pembuatan Kapal Tradisional - Aguswandi Aguswandi; Muftil Badri; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Recently, it has been difficult to get the wood as a material to construct the traditional ships. Alternatively, the wood can be substituted by composite materials such as the composite of coco fiber. The coco fiber composites have potential to construct a fishing boat. In this research produced the composite plates and investigation of their value of tensile strength and flexural strength. The composite composition was used 70% polyester and 30% coco fiber. Production of the composite plates used Vacuum Assisted Resin Infusion (VARI) method by variation of the direction of fibers (random, continous and woven). Based on the research result that was produced the composite plates sizes of 400 x 400 x 8 mm and the value of tensile strengths of composite coco fiber for random fiber direction of 12.8572 N/mm2, continuous fiber direction of 15.4436 N/mm2 and woven direction of 12.1797 N/mm2. The value of flexural strengths for random fiber direction was 97.3220 N/mm2, continuous fiber direction of 96.1347 N/mm2 and woven fiber direction of 80.3922 N/mm2. In conclusion, the value of the highest tensile strength and the highest flexural strength were a continuous fiber direction and a random fiber direction, respectively.Keywords: Composites, Coco Fiber, VARI.